Breaking down the cell wall: Still an attractive antibacterial strategy - Zhou, Jingxuan; Cai, Yi; Liu, Ying; An, Haoyue; Deng, Kaihong; Ashraf, Muhammad Awais; Zou, Lili; Wang, Jun (Frontiers in Microbiology, 2022)
Since the advent of penicillin, humans have known about and explored the phenomenon of bacterial inhibition via antibiotics. However, with changes in the global environment and the abuse of antibiotics, resistance mechanisms have been selected in bacteria, presenting huge threats and challenges to the global medical and health system. Thus, the study and development of new antimicrobials is of unprecedented urgency and difficulty. Bacteria surround themselves with a cell wall to maintain cell rigidity and protect against environmental insults. Humans have taken advantage of antibiotics to target the bacterial cell wall, yielding some of the most widely used antibiotics to date. The cell wall is essential for bacterial growth and virulence but is absent from humans, remaining a high-priority target for antibiotic screening throughout the antibiotic era. Here, we review the extensively studied targets, i.e., MurA, MurB, MurC, MurD, MurE, MurF, Alr, Ddl, MurI, MurG, lipid A, and BamA in the cell wall, starting from the very beginning to the latest developments to elucidate antimicrobial screening. Furthermore, recent advances, including MraY and MsbA in peptidoglycan and lipopolysaccharide, and tagO, LtaS, LspA, Lgt, Lnt, Tol-Pal, MntC, and OspA in teichoic acid and lipoprotein, have also been profoundly discussed. The review further highlights that the application of new methods such as macromolecular labeling, compound libraries construction, and structure-based drug design will inspire researchers to screen ideal antibiotics.